Coastal shrimp aquaculture in Thailand key issues for research. - Smith, P.T. (ed.). (Canberra, Australia ACIAR, 1999)
ACIAR Technical Reports no. 47
Keywords: Thailand; PENAEUS MONODON; Shrimps; Giant tiger shrimp culture--Thailand--Congresses.